An Intranasal Vaccine Based on Outer Membrane Vesicles Against SARS-CoV-2 - Thapa, Himadri B.; Müller, Anna M.; Camilli, Andrew; Schild, Stefan (Frontiers in Microbiology, 2021)
The prevailing pandemic of SARS-CoV-2 highlights the desperate need of alternative vaccine-platforms, which are safe, effective, and can be modified to carry antigens of emerging pathogens. The current SARS-CoV-2 vaccines based on mRNA and adenoviral vector technology meet some of these criteria, but still face limitations regarding administration route, mass production, stability and storage. Herein, we introduce a novel SARS-CoV-2 vaccine candidate based on bacterial outer membrane vesicles (OMVs). Vibrio cholerae and enterotoxigenic Escherichia coli (ETEC) have been genetically modified to produce increased amounts of detoxified OMVs decorated with the receptor binding domain (RBD) of the SARS-CoV-2 Spike protein. Intranasal immunization with RBD-decorated OMVs not only induced a robust immune response against the bacterial outer membrane components, but also detectable antibody titers against the Spike protein. Cell culture infection assays using a Spike-pseudotyped lentivirus confirmed the presence of SARS-CoV-2 neutralizing antibodies. Highest titers against the SARS-CoV-2 Spike protein and most potent neutralization activity was observed for an alternating immunization regimen using RBD-decorated OMVs from ETEC and V. cholerae in turn. These results highlight the versatile vaccine applications offered by OMVs via expression of heterologous antigens in the donor bacterium.